RECONSTRUCTION MICROSURGICAL TUBAL STERILIZATION POST - Soihet, Samoel (2015)
72 cases of patients who underwent recanalization after tubal sterilization, which analyzed the results are studied. Postpartum 9.2%, 37.5% during caesarean section and 33.3% by minilaparotomy. All were subjected to the technique of Pomeroy. A new engagement or the loss of children, were the main causes of reconstruction. Only 54 cases were followed 45 pregnancies that occurred between 8 and 28 months after surgery. The most important problem tubal ectopic pregnancies were 9.2%. The best results were in tubes longer than 7 centimeters and those of ítsmica itsmico anastomosis. It must be preserved during the surgical sterilization horn as much as possible, avoid sterilization cautery and remember what is probably the last chance to restore fertility.